Exploring character conflict in molecular data - Cruickshank, Robert H. (Zootaxa, 2011)
Mooi & Gill (2010) have made a number of criticisms of statistical approaches to the phylogenetic analysis of molecular data as it is currently practiced. There are many different uses for molecular phylogenies, and for most of them statistical methods are entirely appropriate, but for taxonomic purposes the way that these methods have been used is questionable. In these cases it is necessary to introduce an extra step into the analysis – exploration of character conflict. Existing methods for exploring character conflict in molecular data such as spectral analysis, phylogenetic networks, likelihood mapping and sliding window analyses are briefly reviewed, but there is also a need for development of new tools to facilitate the analysis of large data sets. Incorporation of previous phylogenies as priors in Bayesian analyses could help to provide taxonomic stability, while still leaving room for new data to alter these conclusions if they contain sufficiently strong phylogenetic signal. Molecular phylogeneticists should make a clearer distinction between the different uses to which their phylogenies are put; methods suitable in one context may not be appropriate in others.